Character Education Through Learning to Appreciate the Drama of the Stretcher Bearer by Gepeng Nugroho - Sholikah, Amilatus; Fatoni, Akhmad (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to strengthen students' character education through learning drama appreciation using video media. The activity was held at SDN Pagerejo, Gedeg District, Mojokerto Regency, in November 2024 with 40 students in grades IV and V. The type of research method used is participatory, where students watch a video of the drama The Stretcher Bearer which contains moral values such as responsibility, empathy, cooperation, and loyalty. Then, students discuss to analyze character and moral messages and reflect on their application in daily life. The results showed an improvement in critical thinking, communication, empathy, and social awareness. This learning is effective in supporting character education in elementary schools.